PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INVESTIGASI KELOMPOK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS X SMAN BUKITTINGGI - Majidah Khairani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2016)
This study aims to mathematical problem solving ability of students after being given treatment model of cooperative learning investigative research design used in this study is a quasi-experimental research and shaped "Randomized Control Group Only Design". Subjects in this study were students X5 and class X2 SMAN 2 Bukittinggi. The data collection is done by giving the test. From the results of research and discussion obtained an average value of problem-solving abilities in class 78 and class control experiment 69.59 Value Standard deviation of the experimental class is smaller than the control class. This indicates that the value of the experimental class is more spread out close to the average than the control class. Through statistical test average difference can be concluded that the mathematical problem solving ability of students taught using learning model Investigation better than the results of student learning with conventional learning in class X SMAN 2 Bukittinggi 2014/2015.